Utilization of tanniniferous feeds. 4. Effect of supplementation of Acacia nilotica pods on nutrient utilization and extent of tannin degradation in cattle - BARMAN, K; RAI, S N (The Indian Journal of Animal Sciences, 2011)
Crossbred (Karan Fries and Karan Swiss, 205 to 223 kg body weight) male cattle (12) have been grouped into 4 of 3 animals each in a randomized block design. Four concentrate mixtures containing 0, 31, 62 and 93% Acacia pods (w/w), equivalent to 0, 4, 8 and 12% tannins in total diets were used to evaluate the supplementation of Acacia pods on nutrient utilization and extend of tannin degradation. Animals were supplemented with concentrate and oat hay at the ratio of 70: 30. The dry matter (DM) intake was not affected by supplementation of Acacia pods up to 62% in the concentrate mixture. The digestibility of DM was not affected by supplementation of Acacia pods up to 31% but reduced there. Similarly, organic matter (OM), crude protein (CP), ether extract (EE), nitrogen free extract (NFE) and hemicellulose digestibility was not affected by inclusion of Acacia pods up to 31% in the concentrate mixture but reduced thereafter. Crude fiber (CF), acid detergent fiber (ADF) and cellulose digestibility remained similar for all levels of supplementation of pods in the concentrate mixture. Digestible crude protein (DCP) and total digestible nutrient (TDN) intake (kg/d; g/kg WO.7S) remained unaffected by Acacia pods supplementation up to 31% level in the concentrate mixture but reduced thereafter. The absorbed nitrogen as % intake and biological value of dietary protein remained similar at 0 and 31%level of Acacia pods supplementation but reduced thereafter. The nitrogen balance showed declined in trend with increased level of Acacia pods in the diet. However, N balance remained similar at 0 and 31% supplementation of pods. The extent of tannin degradation was ranging from 89.75 to 96.37% in different diets. It is concluded that Acacia pods can be incorporated safely in the concentrate mixture of cattle up to 31% with out affecting the nutrient intake and their utilization. Â